Turisztikai desztinációs menedzsment kialakítása az ukrán-magyar határrégióban - Tarpai, József (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The overall objective of this study is to create a competitive and sustainable tourism destination in the border area of Hungary (Szabolcs-Szatmár-Bereg) and the Ukraine (Zakarpattya). This destination should offer a complex visitor experience for the tourists arriv-ing to the area. In order to reach the general objective two specific objectives shall be met: create a professional Tourism Destination Management Organisation with relevant compe-tence of for the project area; carry out complex tourism projects in the project area in order to increase the competitiveness of the tourism attractions. From tourism point of view a general and effective marketing activity for the region is missing, potential visitors simply do not know why to come to the area.